2020
DOI: 10.1039/d0ra02848g
|View full text |Cite|
|
Sign up to set email alerts
|

A sensitive OFF–ON–OFF fluorescent probe for the cascade sensing of Al3+ and F ions in aqueous media and living cells

Abstract: A simple Schiff-base ligand 2-hydroxy-1-naphthaldehyde semicarbazone (HNS) was synthesized and applied to the sequential sensing of Al3+ and F− ions in aqueous media and live cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…A naphthaldehyde‐semicarbazone Schiff base ( L23 ) was also found to function as a fluorescence “turn on” sensor for Al 3+ in buffered aqueous media, thanks to the combined effect of inhibition of CH=N isomerization and chelation enhanced fluorescence (CHEF) [78] . Considerable increment in the emission intensity was detected only in the presence of Al 3+ .…”
Section: Fluorescent Bioimaging Applicationmentioning
confidence: 99%
“…A naphthaldehyde‐semicarbazone Schiff base ( L23 ) was also found to function as a fluorescence “turn on” sensor for Al 3+ in buffered aqueous media, thanks to the combined effect of inhibition of CH=N isomerization and chelation enhanced fluorescence (CHEF) [78] . Considerable increment in the emission intensity was detected only in the presence of Al 3+ .…”
Section: Fluorescent Bioimaging Applicationmentioning
confidence: 99%
“…Most of them used F − to dissociate the metal ions in the coordinate probe‐metal ions to produce a free probe, and then the fluorescence returns to the original level. [ 33–35 ] However, a probe for simultaneous detection of these three ions has never been reported. Therefore, there is an urgent need to develop a probe with multiple recognition capability for In 3+ , Fe 3+ and F − .…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectra of 18-Al 3+ also conrm the binding ratio by showing a peak at m/z 483.1361 corresponding to 18 + Al 3+ − 2H + [calcd, m/z: 483.1345] because of the deportation of the phenolic group -OH of 18. 54 Wang et al described a Schiff-base compound series with N, O, and S donor atoms for selective recognition of Au 3+ ions. 55 The sensing mechanism was achieved via a two-step Au 3+induced hydrolysis reaction.…”
Section: Methodsmentioning
confidence: 99%
“…On further investigation, it was revealed that the 18 –Al 3+ complex could recognize F − ions to a great extent through a metal displacement approach. 54 Probe 18 and its Al 3+ -based complex show high selectivity and sensitivity towards Al 3+ and F − ions, and the detection limit for Al 3+ and F − was found to be 6.75 × 10 −8 M and 7.89 × 10 −7 M, respectively. With Al 3+ , a red shift with two isosbestic points in the spectra of 18 was observed, with a significant fluorescence enhancement coinciding with the blue shift of emission maxima (Fig.…”
Section: Fundamental Of the Cn Bond Isomerization Concept Of The Sens...mentioning
confidence: 97%